2005
DOI: 10.1177/0886260505278107
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Abuse in Childhood and Interpersonal Violence in Adulthood

Abstract: This study investigates the cumulative impact of sexual abuse in childhood and adult interpersonal violence in the past year on depressive symptoms in a nonclinical sample of 265 primarily African American (74%) women. The frequency of depressive symptoms, measured by the Center for Epidemiologic Studies Depression Scale (CES-D), was highest for women who experienced both forms of victimization. Women who reported greater stress over life's daily hassles reported more depressive symptoms. Women with higher lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 49 publications
4
48
1
Order By: Relevance
“…A national survey indicated decreased mental illness with more positive support (Coker et al, 2002a), and smaller studies also found less distress (Humphreys et al, 2001), as well as fewer mood disorders and increased resilience scores (Schultz et al, 2009). Additionally, decreased rates of depression were found if women received more family support (McGuigan & Middlemiss, 2005).…”
Section: B) Supports Availablementioning
confidence: 98%
“…A national survey indicated decreased mental illness with more positive support (Coker et al, 2002a), and smaller studies also found less distress (Humphreys et al, 2001), as well as fewer mood disorders and increased resilience scores (Schultz et al, 2009). Additionally, decreased rates of depression were found if women received more family support (McGuigan & Middlemiss, 2005).…”
Section: B) Supports Availablementioning
confidence: 98%
“…Although some women may internalize abusive experiences in a highly contained way, which manifest through clinical diagnoses such as depression (McGuigan and Middlemiss 2005;Sullivan et al 2005) or anorexia-nervosa (Laporte and Guttman 2001), along with acts of self-mutilation (Currier 2004), other women may externalize those experiences through rage that involves acts of violence and aggression (Flemke 2006;Flemke and Allen 2008). What was learned from this particular group of women was that triggers for rage may be rooted in past wounds of abuse and other victimization.…”
Section: Discussionmentioning
confidence: 95%
“…Revictimization often worsens these problems (Classen, Palesh, & Aggarwal, 2005;Messman & Long, 1996). Although different criteria for CSA have been used, studies show that compared to women who have been sexually victimized only in childhood, revictimized women report higher levels of distress (Messman-Moore, Long, & Siegfried, 2000), more symptoms from the Trauma Symptom Checklist (Follette, Polusny, Bechtle, & Naugle, 1996;Gold, Milan, Mayall, & Johnson, 1994), more depressive symptoms (McGuigan & Middlemiss, 2005), and more interpersonal problems (Classen et al, 2001). Women who have been revictimized are also more likely to have a lifetime diagnosis of Post Traumatic Stress Disorder (PTSD) compared to women abused only in childhood (Arata, 1999), and to have attempted suicide compared to women assaulted only as an adult (Cloitre, Scarvalone, Difede, 1997).…”
Section: Severity Of Consequences Of Abusementioning
confidence: 99%